The Monro-Kellie Doctrine: A Review and Call for Revision - Benson, J.C.; Madhavan, A.A.; Cutsforth-Gregory, J.K.; Johnson, D.R.; Carr, C.M. (American Journal of Neuroradiology, 2022)
SUMMARY: The Monro-Kellie doctrine is a well-accepted principle of intracranial hemodynamics. It has undergone few consequential revisions since it was established. Its principle is straightforward: The combined volume of neuronal tissue, blood, and CSF is constant. To maintain homeostatic intracranial pressure, any increase or decrease in one of these elements leads to a reciprocal and opposite change in the others. The Monro-Kellie doctrine assumes a rigid, unadaptable calvaria. Recent studies have disproven this assumption. The skull expands and grows in response to pathologic changes in intracranial pressure. In this review, we outline what is known about calvarial changes in the setting of pressure dysregulation and suggest a revision to the Monro-Kellie doctrine that includes an adaptable skull as a fourth component.IIHidiopathic intracranial hypertensionSIHspontaneous intracranial hypotension